Granulocyte colony-stimulating factor in the treatment of acute radiation syndrome: a concise review - Hofer, Michal; Pospíšil, Milan; Komůrková, Denisa; Hoferová, Zuzana (Molecules (Basel, Switzerland), 2014)
This article concisely summarizes data on the action of one of the principal and best known growth factors, the granulocyte colony-stimulating factor (G-CSF), in a mammalian organism exposed to radiation doses inducing acute radiation syndrome. Highlighted are the topics of its real or anticipated use in radiation accident victims, the timing of its administration, the possibilities of combining G-CSF with other drugs, the ability of other agents to stimulate endogenous G-CSF production, as well as of the capability of this growth factor to ameliorate not only the bone marrow radiation syndrome but also the gastrointestinal radiation syndrome. G-CSF is one of the pivotal drugs in the treatment of radiation accident victims and its employment in this indication can be expected to remain or even grow in the future.
Keywords: rozvrh dávkování léků; Animals; Interleukin-3; Thrombopoietin; thrombopoetin; Time Factors; časové faktory; lidé; Bone Marrow; rekombinantní proteiny; Recombinant Proteins; Drug Administration Schedule; akutní radiační syndrom; membránové proteiny; Acute Radiation Syndrome; faktor stimulující kolonie granulocytů; Granulocyte Colony-Stimulating Factor; kostní dřeň; interleukin-3; únik radioaktivních látek; kombinovaná farmakoterapie; Radioactive Hazard Release; Membrane Proteins; růstový faktor kmenových buněk; zvířata; Stem Cell Factor; Drug Therapy, Combination; Humans